2009
DOI: 10.1007/s12529-009-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anxiety and Depression in Danish Cardiac Patients with a Type D personality: Cross-Validation of the Type D Scale (DS14)

Abstract: Background Type D personality is an emerging risk factor in cardiovascular disease. We examined the psychometric properties of the Danish version of the Type D Scale (DS14) and the impact of Type D on anxiety and depression in cardiac patients. Method Cardiac patients (n=707) completed the DS14, the Hospital Anxiety and Depression Scale, and the Eysenck Personality Questionnaire. A subgroup (n = 318) also completed the DS14 at 3 or 12 weeks. Results The two-factor structure of the DS14 was confirmed; the subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
62
5
18

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 53 publications
17
62
5
18
Order By: Relevance
“…Результаты предыдущих работ показали положи-тельную корреляцию между NA и SI c уровнями тре-воги, депрессии [16], враждебности [14], что хорошо сочетается с результатами нашего исследования. Обратная корреляционная зависимость была обнару-жена между SI и экстраверсией [5].…”
Section: Discussionunclassified
“…Результаты предыдущих работ показали положи-тельную корреляцию между NA и SI c уровнями тре-воги, депрессии [16], враждебности [14], что хорошо сочетается с результатами нашего исследования. Обратная корреляционная зависимость была обнару-жена между SI и экстраверсией [5].…”
Section: Discussionunclassified
“…Evidence also shows that after control for depressive symptoms, Type D was associated with ventricular arrhythmia, 52 increased cortisol, 53,54 and oxidative stress 55 in cardiac patients. Further, Type D predicted the onset, 33 prevalence, 36,46,47 persistence, 35,48 and severity 37 of depression and anxiety symptoms in cardiac patients, adjusting for baseline depression scores. In addition, Type D is associated with poor health status and fatigue, 38,[57][58][59][60] adjusting for depressive symptoms.…”
Section: Type D Is Not Depressionmentioning
confidence: 92%
“…42 Factor analysis including the BDI and HADS depression scales confirmed that the items from the 14-item Type D Scale (DS14) 15 were distinctly different from depressive symptoms in cardiac patients. 44 In addition, Type D predicted the onset of depressive symptoms in patients who were free from depression at baseline 33 and predicted the prevalence 46,47 and persistence 48 of depressive symptoms, adjusting for baseline levels of depression.…”
Section: Narrative Review Of Type D Personality and Depressionmentioning
confidence: 99%
“…Regarding health behavior, Spindler et al [23] found no associations of type D with smoking or cardiovascular risk factors in cardiac patients, but in a community sample [4], a slightly reduced rate of healthy diet and physical activity was reported. Regarding health care utilization, inadequate consultation behavior has been reported for them [24,25].…”
Section: Introductionmentioning
confidence: 99%